2015
DOI: 10.1016/j.eurpolymj.2015.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Degradable PEGylated protein conjugates utilizing RAFT polymerization

Abstract: Poly(ethylene glycol) (PEG)-protein therapeutics exhibit enhanced pharmacokinetics, but have drawbacks including decreased protein activities and polymer accumulation in the body. Therefore a major aim for second-generation polymer therapeutics is to introduce degradability into the backbone. Herein we describe the synthesis of poly(poly(ethylene glycol methyl ether methacrylate)) (pPEGMA) degradable polymers with protein-reactive end-groups via reversible addition-fragmentation chain transfer (RAFT) polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…Our group has conjugated a copolymer of 5,6-benzo-2-methylene-1,3-dioxepane (BMDO), a commonly used CKA, and PEGMA to lysozyme whose amines have been thiolated via disulfide exchange. 20 The resulting conjugate was active and the polymer was degradable under a basic condition (5% KOH), which suggests that the polymer could be degraded by ester cleavage in vivo.…”
Section: Selection Of the Polymer To Be Conjugatedmentioning
confidence: 99%
“…Our group has conjugated a copolymer of 5,6-benzo-2-methylene-1,3-dioxepane (BMDO), a commonly used CKA, and PEGMA to lysozyme whose amines have been thiolated via disulfide exchange. 20 The resulting conjugate was active and the polymer was degradable under a basic condition (5% KOH), which suggests that the polymer could be degraded by ester cleavage in vivo.…”
Section: Selection Of the Polymer To Be Conjugatedmentioning
confidence: 99%
“…The M n by 1 H NMR could not be determined accurately because a complete loss of the aldehyde end group was observed. However, we believe that the low molecular weight was not due to cleavage of the backbone during these mild deprotection conditions because treatment with KOH further reduces the molecular weight (Figure S6, Supporting Information), and we have previously shown that BMDO copolymers are stable for greater than 7 d in carbonate solution . Instead, the low M n is likely a result of interactions of the polymer with the GPC column, as we have previously observed with other trehalose polymers …”
Section: Resultsmentioning
confidence: 62%
“…Degradation of p(BMDO‐ co ‐BMA‐trehalose) was evaluated by exposure to a 5% KOH solution. KOH is commonly used to accelerate conditions for polymer degradation . The trehalose copolymer was found to be hydrolytically degradable, and degradation was observed within 24 h as demonstrated by a decrease in GPC molecular weight to 1900 Da (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is presumed that one side of DBCO reacted with 27 kDa scFv and another side of DBCO reacted with lower MW of degraded scFv which has around 19 kDa based on SDS PAGE gel result. in polymer MW [212,213] . Following protein-polymer bioconjugation, we then carried out flow…”
Section: Conjugation Of Azide-modified J591 Scfv Into Dbco Peg Linkermentioning
confidence: 99%